2022
DOI: 10.1007/s11845-022-02984-1
|View full text |Cite
|
Sign up to set email alerts
|

Waning immunity to inactive SARS-CoV-2 vaccine in healthcare workers: booster required

Abstract: Aims Despite high vaccination rates, increasing case numbers continue to be reported with the identification of new variants of concern, and the issue of durability of the vaccine-induced immune response remains hot topic. Real-life data regarding time-dependent immunogenicity of inactivated COVID-19 vaccines are scarce. We aimed to investigate the changes in the antibody at the different times after the second dose of the CoronaVac vaccine. Methods The study included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…In another study, a decrease in antibody titers was observed 3 months after the CoronaVac vaccine. Similar to our study, this decrease was more rapid and significant in those with no previous history of COVID-19 infection 14,15 . In a study of 850 vaccinated participants in Hong Kong, it was reported that the median antibody titers in the BNT162b2 mRNA vaccine group remained above the threshold for 6 months, while the median antibody titers in the CoronaVac vaccine group dropped significantly after 2 months 16 .…”
Section: Discussionsupporting
confidence: 91%
“…In another study, a decrease in antibody titers was observed 3 months after the CoronaVac vaccine. Similar to our study, this decrease was more rapid and significant in those with no previous history of COVID-19 infection 14,15 . In a study of 850 vaccinated participants in Hong Kong, it was reported that the median antibody titers in the BNT162b2 mRNA vaccine group remained above the threshold for 6 months, while the median antibody titers in the CoronaVac vaccine group dropped significantly after 2 months 16 .…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis consistently con rmed a high VE at preventing hospitalizations and deaths, at comparable levels across all vaccines, regardless of VOC (excluding Omicron). Numerous reports of waning antibody levels [48][49][50] have driven the implementation of booster doses in many countries, based primarily on the associated waning of protection against mild infections, manifesting as breakthrough cases in vaccinated individuals [51,52]. Importantly, despite declining antibody levels, we found high and sustained VE against hospitalizations and deaths for AZD1222 and mRNA-based vaccines up to 140 days, with limited waning observed when data enabled informed assessments (Figure 4).…”
Section: Insights On Waning Of Ve or Duration Of Protectionmentioning
confidence: 65%
“…After title and abstract screening, we retrieved 193 full‐text reports for further review. Finally, 11 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 articles met our inclusion criteria. All included studies were of high quality (NOS > 6).…”
Section: Resultsmentioning
confidence: 99%